PSYCHOLOGICAL ART TECHNOLOGY IN ACADEMIC EDUCATION - Kaniuka, I. (Педагогічна освіта: Теорія і практика. Психологія. Педагогіка., 2017)
The author analyses the state of modern education, priorities and objectives for its modernization. Accordingly, it is examined the content of the psychological art techniques as one of the innovative forms of academic research, teaching and learning, it is found out the list of competences and learning outcomes that student acquires within the psychological art techniques, it is described mechanisms and the content of students’ theatre studio activity. Thus, the psychological art technologies in academic education encourage the actualization of such person’s mental resources as creativity, expression, reflection. The participants are taught to express themselves and thus can use this potential in the social communication. The psychological art technologies in academic education have a therapeutic orientation — the unconscious processes of the participants find a way to express themselves when the participants recall the situations from the past, imagine the situations of the present or future, they reflect their fantasies and dreams in the game, the transformation takes place and the participants gain new experience.